(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This research paper aims to investigate the role of technology in distance learning and its impact on enhancing the learning quality of students. The study examines existing literature and research on the effectiveness of technology in delivering quality education regardless of time and place constraints. It also explores the use of interactive methods such as videoconferencing and AI systems to facilitate learner-instructor interaction. The findings highlight the advantages of distance learning, including flexibility, equity, low-cost alternatives, new learning experiences, and expanded resources. However, concerns are raised regarding the potential violation of social boundaries and issues of responsibility, agency, and surveillance associated with the use of AI systems in online learning.